Dynamic Research EvaluAtion for Management, Python version (DREAMpy): open source software for evaluating the economic impacts of agricultural research and development projects - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The pilot is over and the tool is available for use, along with guidelines on how to use it.